Effect of plyometric training on vertical jump performance (A meta-analysis study) - Özdemir, M.; Kayantas, I. (International Journal of Applied Exercise Physiology, 2020)
The main purpose of this study is to determine the effect size of teachers on vertical jump performance of plyometric training. about the effects on vertical jump of plyometric training method in Turkey The Council of Higher Education in the National Thesis Archive, Google academic journals parking graduate has been published on the websites of theses and involved screening method of the research article 31 master's thesis, 5 doctoral thesis and 7 research article 43 studies in accordance with the inclusion criteria were discussed. The total number of samples within the scope of the studies is 1188. In addition, age, training duration, sports branch and publication type variables were analyzed as the moderator who could not participate in the primary research. It is considered that the studies to be included in the research are within certain criteria. Criteria determined for the research; The study is a postgraduate thesis or research article, plyometric training has been studied, there are experimental and control groups in the study, pre-test and post-test data are included, and the arithmetic mean and standarddeviations of the studies are included. Comprehensive Meta-Analysis (CMA) program was used in experimental meta-analysis. According to the meta-analysis data of our study, when the effect of plyometric training on the vertical jump feature was examined, it was found that it had a medium effect size with an effect size of 0.714. For the development of the vertical jump feature, plyometric training can be said to be moderately effective.